Evaluation of arterial stiffness and hemodynamics by oscillometric method in patients with systemic sclerosis - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; ATAŞ, HALİL; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT; DİRESKENELİ, RAFİ HANER (SPRINGER WIEN, 2013)
Arterial stiffness and its hemodynamic consequences are associated with adverse cardiovascular events. Pulse wave velocity (PWV) and augmentation index (AIx) are noninvasive markers of arterial stiffness. Systemic sclerosis (SSc) is a systemic, autoimmune disease affecting mainly the small vessels. The aim of this study was to evaluate the arterial stiffness parameters and hemodynamics by oscillometric method in patients with SSc. Thirty-five consecutive patients with diagnosed SSc and 35 age- and sex-matched healthy controls were included in the study. Measurements of arterial stiffness were carried out by using a Mobil-O-Graph arteriograph system that detected signals from the brachial artery. While hemodynamic parameters were not statistically significant between SSc and control groups, heart rate was significantly higher in SSc group (84 +/- 12 and 72 +/- 7 bpm, p = 0.001). SSc patients had significantly higher AIx and PWV values compared with controls (27.9 +/- 12.4 versus 21.0 +/- 11.4 %, p = 0.019 and 6.56 +/- 1.5 versus 5.04 +/- 0.17 m/s, p < 0.001, respectively). PWV was significantly associated with SSc when adjusted by heart rate (p = 0.001, Odds ratio (OR): 17.304, 95 % confidence interval (CI): 3.225-92.832). PWV and AIx were significantly higher in patients with SSc. Measurement of arterial stiffness parameters using oscillometric method was reliable, reproducible and easy in patients with SSc.
Keywords: Arterial stiffness; Pulse wave velocity; Augmentation index; Systemic sclerosis; Oscillometric method; PULSE-WAVE VELOCITY; CARDIOVASCULAR EVENTS; VASCULAR FUNCTION; BLOOD-PRESSURE; TASK-FORCE; ATHEROSCLEROSIS; RISK; ASSOCIATION; INVOLVEMENT; DYSFUNCTION